A study on correlation between estimation of bilirubin by transcutaneous bilirubinometry and laboratory method (Bangladesh Journal of Medical Science, 2024)
Background: Presently, transcutaneous determination of bilirubin has become a valuable method for the early detection of neonatal  hyperbilirubinemia.  This  study  aims  to  determine  the correlation of transcutaneous bilirubin with serum bilirubin levels  and  assess  the  factors  affecting  transcutaneous  bilirubin measurement in term and late preterm neonates.Materials and Methods: The study included 100 newborns born at a gestational age of 35 to 41 weeks, with a birth weight of 2100 to 3500 g. Simultaneous measurement of bilirubin by traditional (invasive) and transcutaneous (non-invasive) methods was carried out within 15 minutes of admission in the neonatal intensive care unit. Parallel transcutaneous  measurements  were  taken  in  the  forehead  and sternum. Statistical analysis was done to determine the correlation of transcutaneous (forehead and sternal) bilirubin with serum bilirubin  levels  and  assess  the  factors  affecting  transcutaneous bilirubin measurement.Results: In  the  range  of  serum  bilirubin  concentrations  till  15  mg/ dl, a close correlation was observed between serum bilirubin (TSB)  estimated  by  direct  spectrophotometric  method  and transcutaneous bilirubin (TcB) estimated by “Bilitest 2000”. TcB estimation on the sternum was better correlated than that on the forehead  (r-value:  0.962  vs.  0.935).  TcB  had  a  good  correlation with  TSB  across  the  range  of  12.5  -  20.5  mg/dl.  Neonatal hypothermia  significantly  decreased  TcB  estimation  (p  =0.021, F=4.227).  Respiratory  distress,  convulsion,  sclerema  and  shock in neonates did not affect TcB estimation.Conclusion: TcB  has  a  good  correlation  with  TSB  in  term  and  late  preterm neonates. Thus TcB  readings  can  be  used  to  screen  and  manage neonatal hyperbilirubinemia cases.  Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 690-697